Global trends in research output by zoos and aquariums. Issue 6 (30th June 2021) - Escribano, Nora; Ariño, Arturo H.; Pino‐del‐Carpio, Andrea; Galicia, David; Miranda, Rafael
Abstract: Zoos and aquaria, often regarded as preservation‐cum‐entertainment enterprises, are also actors in the effort to curb the biodiversity crisis: raising awareness, supporting conservation, and conducting research. We assessed trends in zoo and aquaria research topics and study organisms over time worldwide. For the zoos and aquaria registered in the Species360's Zoological Information Management System and the World Association of Zoos and Aquariums, we compiled metadata on their research published in the peer‐reviewed literature indexed in Scopus and carried out a keyword frequency analysis. The production of scientific papers by zoos increased at a much faster rate than the average accrual of scientific papers in the literature. Evolution of research themes ran parallel to that of biological sciences (e.g., development of molecular genetics or increased awareness about conservation). The focus of 48.5% of zoo‐led research was on vertebrates, of which mammal research was 33.7%. Whether zoos are effectively contributing to conservation may still be debatable, but our results highlight their institutional efforts to increase knowledge about the species in their care. Abstract : Article impact statement : Research led by zoos has exploded over the last decade, particularly research on conservation and genetics. Abstract : Tendencias Mundiales en la Producción Investigativa de los Zoológicos y Acuarios Resumen: Los zoológicos y los acuarios, con frecuencia considerados empresas de conservación y entretenimiento, también son actores en el esfuerzo por reducir la crisis de la biodiversidad al crear conciencia, apoyar a la conservación y llevar a cabo investigaciones. Evaluamos las tendencias en los temas de investigación y los organismos de estudios en los zoológicos y los acuarios en todo el mundo a través del tiempo. Compilamos los metadatos de las investigaciones realizadas en los zoológicos y acuarios registrados en el Sistema de Manejo de Información Zoológica de Species360 y en la Asociación Mundial de Zoológicos y Acuarios que han sido publicadas en la literatura revisada por pares indexada en Scopus y realizamos un análisis de frecuencias de palabras clave. La producción de artículos científicos por zoológicos se incrementó a una tasa mucho más rápida que la acumulación promedio de artículos científicos en la literatura. La evolución de los temas de investigación fue paralela a la de las ciencias biológicas (p. ej.: desarrollo de la genética molecular o incremento en la conciencia por la conservación). El enfoque del 48.5% de las investigaciones conducidas por los zoológicos estuvo sobre los vertebrados. De este 48.5%, el 33.7% fueron investigaciones sobre mamíferos. Todavía puede debatirse si los zoológicos están contribuyendo efectivamente a la conservación, pero nuestros resultados resaltan sus esfuerzos institucionales por incrementar el conocimiento sobre las especies bajo su cuidado.